Americanização no condicional: brasil nos anos 40 - Tota, Antonio Pedro [UNESP] (Universidade Estadual Paulista (Unesp), 1993)
O objetivo deste artigo é demonstrar as origens do processo do que pode se chamar de americanização da sociedade brasileira. Através de programas de rádio, do cinema, dos cartoons e outras manifestações culturais, o Office of the Coordinator of Inter American Affairs tratou de disseminar uma imagem favorável dos Estados Unidos no Brasil para garantir a unidade pan-americana na luta contra o Eixo.

The main issue of this paper is to demonstrate the roots of a process that can be called the americanization of the Brazilian society. Through radio programmes, movies, cartoons and any other cultural manifestation, the Office of the Coordinator of Inter American Affairs succeeded in spreading a very good image of the USA in Brazil so that it could have the Pan-American union-against the Axis.
Americanization in the conditional: Brazil in the 40ths
Keywords: Americanização; Indústria cultural; Dominação cultural; Rádio; Cinema; Hollywood; Americanization; Cultural industry; Cultural domination; Radio